Circulating levels of maternal plasma cell‐free miR‐21 are associated with maternal body mass index and neonatal birth weight. (14th November 2014) - Miura, Kiyonori; Higashijima, Ai; Hasegawa, Yuri; Abe, Shuhei; Miura, Shoko; Kaneuchi, Masanori; Yoshiura, Koh‐ichiro; Masuzaki, Hideaki
<x xml:space="preserve">Abstract</x> What's already known about this topic? Circulating cell‐free microRNA levels in maternal plasma are measurable. Circulating levels of some microRNAs are associated with pregnancy‐associated disorders. What does this study add? Cell‐free miR‐21 levels in maternal plasma are independent of fetal gender. Neonatal birth weight affects plasma cell‐free miR‐21 levels. Maternal body mass index affects plasma cell‐free miR‐21 levels.